ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERINGKAT OBLIGASI PERUSAHAAN NON- KEUANGAN DI PT PEFINDO - Manurung, Alwinardo Junianta; Terzaghi, Muhammad Titan (Jurnal Cita Ekonomika, 2024)
This research aims to determine: [1] the influence of profitability, [2] the influence of likuidity, [3] the influence of leverage [4] the influence of size firm, on bond level. This type of research is quantitative research. The population in this study were all non- financial companies registered with PT PEFINDO. The sampling method in this study used a purposive sampling technique of 48 companies. Data collection techniques in this study using a complete financial documentation for 2020-2022 period via the official BEI website anda documentation of companybond rating from the official PT PEFINDO website. The data analysis technique uses descriptive statistical analysis, panel data testing, classical assumption test, hypothesis test, coefficient of determination (R test), simultaneous test (F test), partial test (T test)) processed with Eviews 12. The research results show that profitability, size firm, have a positive and significant effect on bond level, while likuidity and leverage have no effect on bond level.